PENGARUH SUKU BUNGA KREDIT, DANA PIHAK KETIGA (DPK), DAN GIRO WAJIB MINIMUM TERHADAP PENYALURAN KREDIT PADA PT. BANK CENTRAL ASIA, TBK. DI INDONESIA TAHUN 2001-2015 - Fitri, Lailatul; Maulida, Yusni; Indrawati, Toti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine how the effect of interest rates on loans , Third Party Fund ( TPF ) and Reserve Requirement (RR) against lending of Bank Central Asia.In this study using secondary data obtained from financial data publication of Bank Central Asia from 2001 to 2015 time span The analytical method used is the Multiple Linear Regression Analysis . Tests conducted on the hypothesis and the reliability of the data (classical assumption) using significant rate of 5 %. From the results of tests performed on the simultaneous study showed that the level of mortgage interest rate , Third Party Funds (TPF)and Reserve Requirement (RR) by F test significant influence is 0.000 .The results partially by t test , to see the test results significant independent variable on the analysis of multiple factors affecting the loan portfolio in the Government -owned banks in Indonesia , it can be seen that the Third Party Funds variables are variables that significantly influence against lending at Bank Central Asia 0.000 By looking at the results of the coefficient of the independent variable interest rates ,Requirement (RR) is a variable that does not significantly influence lending at Bank Central Asia in Indonesia.Keyword : Interest Rate Loans , TPF ( third party funds ), Reserve Requirement (RR)and Lending